The Effects of Eucheuma cottonii on Signaling Pathway Inducing Mucin Synthesis in Rat Lungs Chronically Exposed to Particulate Matter 10 (PM10) Coal Dust - Nia Kania; Elly Mayangsari; Bambang Setiawan; Dian Nugrahenny; Frans Tony; Endang Sri Wahyuni; M. Aris Widodo (Journal of Toxicology)
This study was aimed at investigating the effects of Eucheuma cottonii (EC) in oxidative stress and the signaling for mucin synthesis in rat lungs chronically exposed to coal dust. Coal dust with concomitant oral administration of ethanolic extract of EC at doses of 150 (EC150) or 300 mg/kg BW (EC300) compared to exposed to PM10 coal dust at doses of 6.25 (CD6.25), 12.5 (CD12.5), or 25 mg/m3 (CD25) (an hour daily for 6 months) and nonexposure group (control). The malondialdehyde (MDA), epidermal growth factor (EGF), transforming growth factor (TGF)-α, epidermal growth factor receptor (EGFR), and MUC5AC levels were determined in the lung. The administration of EC300 significantly (p < 0.05) reduced the MDA levels in groups exposed to all doses of coal dust compared to the respective coal dust-exposed nonsupplemented groups. Although not statistically significant,EC reduced the EGF levels and EGFR expressions in CD12.5 and CD25 groups and decreased the TGF-α, level and MUC5AC expression in CD25 group compared to the respective coal dust-exposed nonsupplemented groups. EC was able to decrease oxidative stress and was also able to decrease signaling for mucin synthesis, at least a part, via reducing the ligand in chronic coal dust exposure.